Implementación del sistema contable en el comercial Da y Mo, provincia de Loja, cantón Macará, periodo noviembre diciembre del 2013 - Rodríguez Guerrero, Andrea Estefanía (2015)
This thesis topic entitled " IMPLEMENTATION OF THE ACCOUNTING SYSTEM IN COMMERCIAL DA AND MO CITY MACARA, Province of Loja, PERIOD NOVEMBER AND DECEMBER 2013 “, you will be made in order to meet the economic and financial situation of the trade determine issues that do not allow adequate development of its activities and as a prerequisite for the degree of Engineer in Accounting and Auditing. Accounting is very important because the basis on which financial and management decisions are based. From the smallest businesses to large corporations an accounting process contributes significantly to their growth, which required to be properly applied by professionals to get accurate results. Under this background the "IMPLEMENTATION OF ACCOUNTING SYSTEM IN THE COMMERCIAL AND DA MO, Loja province, Macará canton, NOVEMBER DECEMBER 2013 PERIOD", for it a goals and methods that allowed the development and optimal supply of labor is raised is deemed necessary research. To fulfill the objectives records, accounting records for daily transactions was designed, accounts s plan was developed, using codes to facilitate the identification of assets, liabilities, equity, income and expenses; control of the goods were developed by multiple system account and check the status of it, apply the accounting process in the Initial Inventory, registering property, securities, rights and obligations, managing the assets of the business to determine. Once reached the main goal of this research is the implementation of the accounting system and DA MO and allowed the company to meet its financial and economic situation; It concludes that the trade operates mostly with its own resources, because borrowing is low , achieving a net profit that favors the creation of enterprise value ; the owner information is provided is true and real and will improve its actions , through sound decision-making